Phosphine–borane catalysts for CO2 activation and reduction: a computational study. (18th June 2022) - Kessete, Jenbrie M.; Demissie, Taye B.; Chilume, Misha; Mohammed, Ahmed M.; Andrushchenko, Valery
Abstract : CO2 conversion to value-added chemicals requires efficient catalytic CO2 reduction. Activation of CO2 using 14 phosphine–borane frustrated Lewis pair catalysts was done computationally using B3LYP-D3/6-31++G(d, p)/PCM/THF and M06-2X/6-311++G(d, p)/PCM/THF methods. We designed 14 catalysts, 12 of which exhibit better catalytic activity towards CO2 activation. Moreover, the catalytic mechanisms of compounds 12 and 4 were predicted, and they showed an efficient catalytic system for CO2 reduction to CO, HCHO and HCOOH. Catalysts 2, 3 and 4, with the same methylene linker, have activation energies of 20.5, 18.3 and 10.4 kcal/mol, respectively. This indicates that the catalytic activity of the compound is highly influenced by the ligand bound to borane and phosphine. Compound 4 with the CO2 activation energy of 10.4 kcal/mol is the most efficient catalyst for CO2 activation ever reported among phosphine–borane catalysts. The energy barriers for H2 activation with catalyst 12 (Δ G ‡ = 26.6 kcal/mol) and 4 (Δ G ‡ = 34.0 kcal/mol) are higher than the HCOOH releasing activation energy. The designed compounds will help to synthesise efficient metal-free phosphine–borane catalysts. Our results also indicate that phosphine–borane catalysts are promising candidates for CO2 reduction and direct hydrogenation. GRAPHICAL ABSTRACT: UF0001